Simulation and knowledge of action - Dokic, Jérôme, 1965-; Proust, Joëlle (Advances in consciousness research, 2002)
The current debate between theory theory and simulation theory on the nature of mentalisation has reached no consensus yet, although many now think that some hybrid theory is needed. This collection of essays represents an effort at re-evaluating the scope of simulation theory, while also considering areas in which it could be submitted to experimental tests. The volume explores the two main versions of simulation theory, Goldman's introspectionism and Gordon's radical simulationism, and enquires whether they allow a non-circular account of mentalisation. The originality of the volume is to co.